2023
DOI: 10.1155/2023/2634158
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Commonly Used Pesticides on Honeybees (Apis mellifera) in North Gonder of Amhara Region, Ethiopia

Abstract: Global honeybee losses and colony decline are becoming continuous threat to the apicultural industry, as well as, for food security and environmental stability. Although the putative causes are still unclear, extensive exposure of bees to pesticides could be the possible factor for worldwide colony losses. This study was aimed at evaluating the impact of nine commonly used pesticide incidents on adult worker honeybees (A. mellifera) under the laboratory condition, in North Gonder of Amhara region, Ethiopia. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Common symptoms included agitation, narcotic-like states, audible hovering, and crawling behaviors (Ali et al 2023b). Pesticide exposure disrupted bee communication and coordination within colonies, leading to heightened agitation and erratic behavior resembling a narcotic-like state (Abay et al 2023). Additionally, pesticides interfered with sensory perception, causing audible hovering sounds during navigation (Haq et al 2024).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common symptoms included agitation, narcotic-like states, audible hovering, and crawling behaviors (Ali et al 2023b). Pesticide exposure disrupted bee communication and coordination within colonies, leading to heightened agitation and erratic behavior resembling a narcotic-like state (Abay et al 2023). Additionally, pesticides interfered with sensory perception, causing audible hovering sounds during navigation (Haq et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…The primary issue pertains to the persistent accumulation of pesticide residues over time, which can exacerbate the decline of species crucial for pollinating terrestrial ecosystems (Brodschneider et al 2017). Prolonged exposure of honey bees to pesticides can have a significant impact on their well-being and behavior (Anwar et al 2022;Abay et al 2023). Among the various types of pesticides that pose a threat to honey bees, neonicotinoids are particularly hazardous (Fairbrother et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They can be exposed to agrochemicals in different ways: through air particles, eating contaminated food (nectar or pollen), and consuming contaminated water [4,10,29]. Exposures to agrochemicals could lead to INPOs' mortality [5,9], changes in diurnal activity patterns, e.g., foraging behavior, navigation, and visitation frequency, and other sublethal impacts (Table 2). In addition, it has been shown that a number of agrochemicals, including neonicotinoids, and chlorpyrifos, can severely damage INPOs' nervous systems and irreversibly impair their immune systems, which eventually decreases their biodiversity [15,23,25,30].…”
Section: Agrochemical Brief Description Referencementioning
confidence: 99%
“…In diverse ecosystems, encompassing agricultural and protected habitats, insectpollinators (INPOs) are essential invertebrates as they promote biodiversity preservation and the health of ecosystems [1][2][3][4]. INPOs are crucial for the pollination services [5,6], as they support the sustainability of countless flowering plants, such as crops, trees, bushes, herbs, vegetables, and many more [7]. They improve agricultural productivity, enhancing human nutrition and food security through pollination services [1].…”
Section: Introductionmentioning
confidence: 99%
“…Agrochemicals are highly toxic and have rapid knockdown effects against insects, including pollinators at lethal or sublethal concentrations [17]. Lethal effects due to acute exposure to insecticides cause immediate honey bee mortality [18]. Sublethal concentrations can cause impairments to navigation and foraging abilities, communication, reduced learning and memory, and altered reproductive success in honey bees [19][20][21].…”
Section: Introductionmentioning
confidence: 99%